South African women's literature and the ecofeminist perspective - Ewing, Maureen Colleen (Rhodes University, Faculty of Humanities, Department of Literary Studies in English)
A social-constructionist ecofeminist perspective argues that patriarchal society separates the human (or culture) from nature, which causes a false assumption that humanity possesses the right, as a superior species, to dominate nature. This perspective integrates the domination of nature with social conflicts, including but not limited to racial discrimination, gender oppression, and class hierarchies. Understanding how these various forms of oppression interrelate forms the main goal of an ecofeminist perspective. Since the nature-culture, female-male, and whitenonwhite conflicts resonate and interlock throughout South Africa's history, socialconstructionist ecofeminism is an indispensable perspective for analysing South African literature. This thesis takes a social-constructionist ecofeminist approach and applies it to four women authors that write about South African society between the years 1860-1900. This thesis includes the following authors and their works: Olive Schreiner (1855-1920) and two of her novels, The Story of an African Farm (1883) and From Man to Man (published posthumously in 1927); Pauline Smith (1882-1959) and her novel The Beadle (1926); Dalene Matthee (1938- ) and three of her novels, Circles in a Forest (1984), Fiela's Child (1986), and The Mulberry Forest (1987); and Marguerite Poland (1950- ) and one of her novels, Shades (1993). This thesis investigates two women from the time period (Schreiner and Smith) and two women from a late twentieth century perspective (Matthee and Poland) and compares how they depict the natural environment, how they construct gender, and how they interpret class and race power struggles. This thesis concludes that the social-constructionist perspective offers unique insights into these four authors. Schreiner's novels reveal her concerns about gender and racial conflicts in South Africa and her understanding of the nature-culture dichotomy as sustained by Social Darwinism. Smith offers insights into the complex power structures in a rural Afrikaans society that keep women and nonwhite races silent. Matthee writes nature as an active participant in her novels; the social and ecological conflicts emphasise the transformation of the Knysna area. Poland explores the racial tensions, gender conflicts, and environmental concerns that preceded the South African War. Schreiner, Smith, Matthee, and Poland make up a small cross-section of South African literature, but they provide a basis for further discussing the ecofeminist perspective within a South African context.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Ecofeminism in literature; Ecology in literature; Nature in literature; South African fiction -- History and criticism; Smith, Pauline, 1883-1959; Schreiner, Olive, 1855-1920; Matthee, Dalene, 1938-2005; Poland, Marguerite